2017
DOI: 10.3389/fnins.2017.00357
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Cues Provided by Sound Improve Postural Stabilization: Evidence of a Spatial Auditory Map?

Abstract: It has long been suggested that sound plays a role in the postural control process. Few studies however have explored sound and posture interactions. The present paper focuses on the specific impact of audition on posture, seeking to determine the attributes of sound that may be useful for postural purposes. We investigated the postural sway of young, healthy blindfolded subjects in two experiments involving different static auditory environments. In the first experiment, we compared effect on sway in a simple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 35 publications
(62 reference statements)
3
45
0
5
Order By: Relevance
“…The data presented here add to our growing understanding that spatial audition can give a measurable balance improvement in people with normal and impaired hearing . A group of 14 older, experienced bilateral hearing aid users were shown to remain stable for a longer period of time standing on a solid surface or on foam while wearing their hearing aids compared to without .…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…The data presented here add to our growing understanding that spatial audition can give a measurable balance improvement in people with normal and impaired hearing . A group of 14 older, experienced bilateral hearing aid users were shown to remain stable for a longer period of time standing on a solid surface or on foam while wearing their hearing aids compared to without .…”
Section: Discussionmentioning
confidence: 61%
“…24 The data presented here add to our growing understanding that spatial audition can give a measurable balance improvement in people with normal and impaired hearing. [12][13][14] A group of 14 older, experienced bilateral hearing aid users were shown to remain stable for a longer period of time standing on a solid surface or on foam while wearing their hearing aids compared to without. 14 A more recent study, again investigating a population wearing hearing aids, used variability of the center of pressure as a main outcome measure and reported similar results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such results confirm previous experiences showing an increased positive effect of sound stimulation, especially when other sensory inputs, such as vision, are neglected. 34,39 To this end, it is worth noting that some authors have demonstrated an increase, or even the reappearance, of VEMPS signal in operated ears after stapedotomy. 40,41 Hypotheses involving saccular overstimulation, due to proximity to the stapes prosthesis, have been proposed, whereas other studies involving VEMPS found contrasting evidence.…”
Section: Discussionmentioning
confidence: 96%
“…From a physiological standpoint, it could be speculated that the restoration of efficient sound transmission may partially influence postural function, possibly providing subjects with additional information about the surrounding environment to better control body movements; sound may act as a spatial landmark helping integrating other sensory inputs, thus improving overall balance control. 33,34 In this light, it has been proposed that a sound-induced vestibular activation would evoke a vestibulo-postural reflex, influencing balance; 35,36 indeed, previous works highlighted various effects of sound on posture from increased oscillation on the mediolateral (x) plane 35 to reduced sway in the same axis 37 and beneficial effects on anteroposterior (y) oscillations. 38 In our study population, a reduction in postural sway was found in both x and y planes with eyes open as well as closed (Fig.…”
Section: Discussionmentioning
confidence: 99%